1984
DOI: 10.3758/bf03199808
|View full text |Cite
|
Sign up to set email alerts
|

Serial learning, interitem associations, phrasing cues, interference, overshadowing, chunking, memory, and extinction

Abstract: Two experiments indicated that two approaches to serial learning are too extreme-the classical view that it consists only of interitem associations and various recent views that it involves no interitem associations. The novel assumption introduced here was that phrasing cues, normally conceptualized as merely segregating long series into smaller units or chunks, may also enter into associations with items, thereby reducing interitem interference and facilitating serial learning. It was found that one item cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
53
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 36 publications
7
53
0
Order By: Relevance
“…Furthermore, many of the finer details of the results could be accounted for by the additional assumption that phrasing cues overshadowed interitem associations (Stempowski et al, 1999). Stempowski et al's (1999) results, along with those of Capaldi et al (1984), clearly showed that discriminability and overshadowing are important factors mediating phrasing cue effects. On the other hand, evidence in both the rat and human literatures suggests that the correspondence between phrasing cues and sequential element organization may also be important determinants of chunking and phrasing effects.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, many of the finer details of the results could be accounted for by the additional assumption that phrasing cues overshadowed interitem associations (Stempowski et al, 1999). Stempowski et al's (1999) results, along with those of Capaldi et al (1984), clearly showed that discriminability and overshadowing are important factors mediating phrasing cue effects. On the other hand, evidence in both the rat and human literatures suggests that the correspondence between phrasing cues and sequential element organization may also be important determinants of chunking and phrasing effects.…”
mentioning
confidence: 97%
“…Stated another way, rhythmic patterning facilitated sequence recall under conditions of ''good rhythmicity'' defined as phrasing that highlighted boundaries between chunks of equal length (numeric balance) and structured content (structural subgroup-level equivalence, symmetry, and other relations). Capaldi et al (1984) also studied the effects of different phrasing conditions applied to the same pattern of sequential elements. They replicated the effects of spatial cues reported by Fountain et al (1984), but argued that phrasing effects, like other aspects of serial-pattern learning, should be explained by appealing to traditional discrimination learning rather than rulelearning processes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One prominent view of phrasing developed in the rat and pigeon learning and memory literature is that phrasing cues facilitate learning by acting as discriminative cues to facilitate anticipating specific stimuli, responses, or sequences of stimuli or responses (Capaldi, Verry, Nawrocki , & Miller, 1984;Terrace, 1987). According to this view, phrasing cues facilitate learning by reducing interference in memory for items in sequence (Capaldi et aI., 1984) or by signaling specific events (Capaldi et aI.…”
Section: Discussionmentioning
confidence: 99%
“…One might hypothesize that phrasing cues could serve at least two roles: They could signal the termination of a chunk, perhaps through overshadowing as suggested by Capaldi et aL (1984), and they could also signal the proper response on the forthcoming trial, namely, the first element of the chunk to come. For mice, it was observed that phrasing cues reduced overextension errors-as if mice knew to discontinue using the within-chunk "+1" or "move-one-to-the-right" response rule.…”
Section: Discussionmentioning
confidence: 99%